Migration Ability of Multipotent Mesenchymal Stromal Cells in Cultivation with Relief Calcium Phosphate Coating - Litvinova, Larysa S.; Shchupletsova, V. V.; Khaziakhmatova, O. G.; Yurova, K. A.; Malashchenko, V. V.; Todosenko, Natalia M.; Khlusova, M. Yu.; Sharkeyev, Yu. P.; Komarova, E. G.; Sedelnikova, M. B.; Chaykina, M. V.; Khlusov, I. A. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(1): 089–093